Evaluation of anaerobic performance in alpine skiers - Maffiuletti, N.; Mognoni, P.; Impellizzeri, F.; Rampinini, E.; Bizzini, M. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: The overall anaerobic contribution (alactic plus lactic) to energy metabolism during alpine skiing (special slalom and giant slalom) has been estimated to be about 65%, i.e., 25-30% by utilization of alactic energy stores and 40% by lactic acid production (Veicsteinas et al. 1984). Some investigators have indeed attempted to predict the skiing performance on the basis of anaerobic assessments, mainly by comparing maximal strength and power of the lower limb muscles between alpine skiers of different levels. The majority of these studies indicated that anaerobic power tests appear to be better predictors of alpine skiing ability compared with the aerobic power tests (White and Johnson 1991). The objectives of the present critical review are directed at examining the different methods of anaerobic performance evaluation in alpine skiing and the main results obtained with competitive athletes, in order to improve the specificity of testing protocols for ski racers and to suggest areas of applied research for the future. Methods: The following variables have been quantified in previous skiing research studies: (i) maximal isometric and isokinetic (mainly concentric) torque of the knee extensor and flexor muscles, (ii) maximal anaerobic power (and capacity) during cycling (Wingate test, from 30 to 90 s), stair climbing (Margaria-Kalamen test) and jumping activities (single and repeated vertical and horizontal jumps). Since technical skill is an important factor influencing the anaerobic energy contribution in alpine skiing, an on-site test battery including sport-specific movements has been developed by the Canadian Ski Federation (Andersen et al. 1990) and by the United States Ski Association (White and Johnson 1991). Anaerobic performance of alpine skiers from different nations and levels of practice has been related to three main skiing performance indices: (i) predefined classifications based on racing accomplishments (e.g., national versus divisional teams), (ii) on-snow time trials, and (iii)"Fédération Internationale de Ski" (FIS) point rankings. We have also collected data from the national Swiss team (50 female and 10 male athletes) and Italian team (37 female and 47 male athletes) by using a force platform (single and repeated vertical jumps) and an isokinetic device (concentric and eccentric actions of the thigh muscles). Results: Even if some investigators have observed significant correlations between skiing performance and laboratory-based (White and Johnson 1993) or field-based (Andersen et al. 1990) assessment of anaerobic performance, others have failed to obtain such a direct relation and have suggested that no singular feature can be used to judge the potential success for an Alpine ski racer (Bacharach and von Duvillard 1995). This conclusion is clearly substantiated by our findings obtained from a large group of Swiss and Italian elite athletes from both sexes. Discussion/Conclusion: In the evaluation of anaerobic performance of athletes, it is imperative to respect the principle of specificity between the testing procedures and the actual demand of the sport. We consider that the majority of the anaerobic tests proposed in previous skiing research do not utilise skiing muscles and movements in a sport-specific manner. Some considerations on the specificity of alpine skiing, based on previous biomechanics research (Berg and Eiken 1999, Muller et al. 2000), are required for future studies in this area. - The type of muscle action: skiing is characterised by stretch shortening cycle with a marked predominance of eccentric over concentric muscle actions in terms of intensity and duration (consider, e.g., the low specificity of cycling tests). - The contraction velocity: knee angular velocity of the outside leg ranges from ~20°/s (super G) to ~70°/s (slalom), i.e., dominance of slow eccentric muscle actions (e.g., low specificity of isokinetic tests). - The knee joint position: knee angles comprised between 60° and 115° (180° = knee fully extended) have been observed during speed and technical skiing events (e.g., low specificity of vertical jump tests, where knee joint angle typically ranges between 90° and 180°). - The contraction "asymmetry": during a turn, ground reaction force (and also knee angle) of the outside leg is extremely different from the inside leg (2.5 versus 1.5 times body weight), so that skiing could be defined as an asymmetrical activity (e.g., low specificity of testing but also training methods based on bilateral, simultaneous and equal-force contractions). - The event specificity: alpine skiing events are extremely different in terms of duration, type and intensity of muscle action, knee joint angle, technical skill, etc. Athletes from speed and technical events should be tested differently.